The relation of work-related factors with ambulatory blood pressure and nocturnal blood pressure dipping among aging workers - Karelius S.; Vahtera J.; Pentti J.; Lindroos A.; Jousilahti P.; Heinonen O.; Stenholm S.; Niiranen T. (Springer, 2022)
Objectives: Individuals with reduced nocturnal blood pressure (BP) dipping are at increased risk of cardiovascular disease compared to persons with normal BP dipping. Although the relation of work-related factors and BP has been studied extensively, very little is known of the association between work-related factors and 24-h BP patterns in aging workers. We examined the cross-sectional relation of work-related risk factors, including occupational status, work-time mode, job demands and job control, with ambulatory BP in aging workers, focusing on nocturnal BP dipping.
Methods: 208 workers (mean age 62 ± 3 years; 75% women) from two Finnish population-based cohort studies underwent 24-h ambulatory BP monitoring. Work-related factors were inquired using a questionnaire. Nocturnal BP dipping was calculated as [1 − (asleep BP/awake BP)] × 100.
Results: Shift workers demonstrated a higher nocturnal diastolic BP dipping than regular day workers (19% vs. 17%, p = 0.03) and had a significantly higher systolic awake BP than regular day workers (136.5 mmHg vs. 132.5 mmHg, p = 0.03). Participants with high job demands demonstrated a smaller nocturnal systolic BP dipping than participants with low job demands (14% vs. 16%, p = 0.04). We did not observe significant differences in nocturnal systolic or diastolic BP dipping between groups categorized by occupational status or job control.
Conclusions: Although shift workers have a higher daytime BP than regular daytime workers, they exhibit greater nighttime BP dipping. Participants with high job demand had smaller nighttime BP dipping than participants with low job demand. Job control or occupation did not affect the 24-h ambulatory BP profile of aging workers.